This I Believe - Lyon, P. H. B. (Percy Hugh Beverley) (Tufts Archival Research Center, 2006)
Hugh Lyon, former Headmaster of Rugby School, talks about God and man and explains that the noble qualities of man, such as love, and vlaor and heroism, prove that he must be the children of God, and God gives life meaning and purpose. In addition, this essay contains an advertisement for a This I Believe LP album.